Mesophyll Abscisic Acid Restrains Early Growth and Flowering But Does Not Directly Suppress Photosynthesis. Issue 2 (25th March 2019) - Negin, Boaz; Yaaran, Adi; Kelly, Gilor; Zait, Yotam; Moshelion, Menachem
Abstract : Basal green tissue ABA widely affects plant morphology, water relations, and growth, inhibiting early growth and flowering, and does not directly suppress photosynthesis in the short term. Abstract: Abscisic acid (ABA) levels increase significantly in plants under stress conditions, and ABA is thought to serve as a key stress-response regulator. However, the direct effect of ABA on photosynthesis and the effect of mesophyll ABA on yield under both well-watered and drought conditions are still the subject of debate. Here, we examined this issue using transgenic Arabidopsis ( Arabidopsis thaliana ) plants carrying a dominant ABA-signaling inhibitor under the control of a mesophyll-specific promoter ( FBPase::abi1-1, abbreviated to fa ). Under normal conditions, fa plants displayed slightly higher stomatal conductance and carbon assimilation than wild-type plants; however, these parameters were comparable following ABA treatment. These observations suggest that ABA does not directly inhibit photosynthesis in the short term. The fa plants also exhibited a variety of altered phenotypes under optimal conditions, including more vigorous initial growth, earlier flowering, smaller flowers, and delayed chlorophyll degradation. Furthermore, under optimal conditions, fa plant seed production was less than a third of that observed for the wild type. However, under drought conditions, wild-type and fa seed yields were similar due to a significant reduction in wild-type seed and no reduction in fa seed. These findings suggest that endogenous basal ABA inhibits a stress-escape response under nonstressed conditions, allowing plants to accumulate biomass and maximize yield. The lack of a correlation between flowering time and plant biomass combined with delayed chlorophyll degradation suggests that this stress-escape behavior is regulated independently and upstream of other ABA-induced effects such as rapid growth and flowering.